Immediate impacts of COVID‐19 on female and male farmers in central Myanmar: Phone‐based household survey evidence. (3rd May 2021) - Ragasa, Catherine; Lambrecht, Isabel; Mahrt, Kristi; Aung, Zin Wai; Wang, Michael
Abstract: This article provides evidence of the immediate impacts of the first months of the COVID‐19 crisis on farming communities in central Myanmar using baseline data from January 2020 and follow‐up phone survey data from June 2020 with 1, 072 women and men. Heterogeneous effects among households are observed. Fifty‐one percent of the sample households experienced income loss from various livelihood activities, and landless households were more severely affected by the crisis, mainly because of lost farm and nonfarm employment and negative impacts on rural enterprises. Women and men in these landless households were equally engaged and affected by lower wages or more difficulties in finding farm work; fewer women were engaged in nonfarm work, but almost all of them lost such nonfarm wage employment. Women in landless households are also particularly vulnerable in terms of worsened workload and increased tension in the household during COVID‐19. Landed households were also affected through lower prices, lower demand for crops, and difficulties in input access. Women and men differ in levels of stress, fear, and pessimism regarding the effects of COVID‐19. In most households, there were no signs that household task‐sharing and work balance improved, and no clear shift in intrahousehold relations was observed.